2021
DOI: 10.1163/22941932-bja10068
|View full text |Cite
|
Sign up to set email alerts
|

Variations in bacterial decay between cell types and between cell wall regions in waterlogged archaeological wood excavated in the intertidal zone

Abstract: The bacterial decay of waterlogged archeological wood (WAW, hard pine spp.) taken from Daebudo shipwreck No. 2, which was buried in the intertidal zone in the mid-west coast (Yellow sea) of South Korea approximately 800 years ago, was investigated. The maximum moisture content of the outer parts (approx. 3 cm of depth) of WAW was approximately 4.2 times higher than that of undegraded reference pine wood. ATR-FTIR and solid-state 13C-NMR analysis indicated a relative increase of the lignin concentration in WAW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 40 publications
1
25
0
2
Order By: Relevance
“…This clearly indicates that these fungi are not ligninolytic or are less so. Some brown-rot fungi can only change the lignin structure [55,56] and could therefore also fall under this category. Unfortunately, no clear evidence for a brown-rot infestation could be found.…”
Section: Morphological Decay Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…This clearly indicates that these fungi are not ligninolytic or are less so. Some brown-rot fungi can only change the lignin structure [55,56] and could therefore also fall under this category. Unfortunately, no clear evidence for a brown-rot infestation could be found.…”
Section: Morphological Decay Patternmentioning
confidence: 99%
“…The ray parenchyma contains a higher quantity of sugars in comparison with fibers and vessels, as they are part of the nutrient reserves of the trees [21], and it is expected that those cells are susceptible to various degrading agents. Very recently, Cha et al [56] revealed that the degradation of the parenchymal cell wall is delayed relative to its adjacent tracheas when they are exposed to erosion bacteria. However, it did not exhibit entire resistance to bacterial decay.…”
Section: Morphological Decay Patternmentioning
confidence: 99%
“…Wood-degrading microorganisms (soft-rot fungi and bacteria) that are present in water-saturated and waterlogged woods can readily depolymerise cellulosic and hemicellulosic components but differ in their ability to modify lignin, a recalcitrant component of the cell wall. Therefore, it is important to have knowledge of the concentration and distribution of lignin in various cell wall regions and tissues in order to understand the degradability of different cell wall layers/structures (e.g., vestures, warts), wood types (hardwood, softwood, normal wood, reaction wood) and cell types [18,29].…”
Section: Cell Wall Compositionmentioning
confidence: 99%
“…Partial waterlogging can support the activity of soft-rot fungi and wood degrading bacteria [6]. However, when exposure conditions become anoxic due to complete waterlogging, for example, in deep ocean waters, ocean, river and lake sediments, and mud, wood is mainly degraded by erosion bacteria [7][8][9][10][11][12][13][14][15][16][17][18]. Soft-rot fungi and tunnelling bacteria may also be present but are much less frequent [13,14,16,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation